Role of the Anti-Sigma Factor SpoIIAB in Regulation of σ(G) during Bacillus subtilis Sporulation - Serrano, Mónica (American Society for Microbiology, 2004)
RNA polymerase sigma factor σ(F) initiates the prespore-specific program of gene expression during Bacillus subtilis sporulation. σ(F) governs transcription of spoIIIG, encoding the late prespore-specific regulator σ(G). However, transcription of spoIIIG is delayed relative to other genes under the control of σ(F), and after synthesis, σ(G) is initially kept in an inactive form. Activation of σ(G) requires the complete engulfment of the prespore by the mother cell and expression of the spoIIIA and spoIIIJ loci. We screened for random mutations in spoIIIG that bypassed the requirement for spoIIIA for the activation of σ(G). We found a mutation (spoIIIGE156K) that resulted in an amino acid substitution at position 156, which is adjacent to the position of a mutation (E155K) previously shown to prevent interaction of SpoIIAB with σ(G). Comparative modelling techniques and in vivo studies suggested that the spoIIIGE156K mutation interferes with the interaction of SpoIIAB with σ(G). The σ(GE156K) isoform restored σ(G)-directed gene expression to spoIIIA mutant cells. However, expression of sspE-lacZ in the spoIIIA spoIIIGE156K double mutant was delayed relative to completion of the engulfment process and was not confined to the prespore. Rather, β-galactosidase accumulated throughout the entire cell at late times in development. This suggests that the activity of σ(GE156K) is still regulated in the prespore of a spoIIIA mutant, but not by SpoIIAB. In agreement with this suggestion, we also found that expression of spoIIIGE156K from the promoter for the early prespore-specific gene spoIIQ still resulted in sspE-lacZ induction at the normal time during sporulation, coincidently with completion of the engulfment process. In contrast, transcription of spoIIIGE156K, but not of the wild-type spoIIIG gene, from the mother cell-specific spoIID promoter permitted the rapid induction of sspE-lacZ expression. Together, the results suggest that SpoIIAB is either redundant or has no role in the regulation of σ(G) in the prespore.